STRATEGI BISNIS PT PERTAMINA DALAM MENGAMBIL ALIH HAK EKSPLORASI MIGAS DARI PT TOTAL EXPLORATION DI BLOK MAHAKAM TAHUN 2015 - Lassa Alam Bijaksana; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the strategy of Pertamina Company in take controll of fuel and oil exploration rights from Total Exploration and Production Company in Mahakam Bloc in 2015. Mahakam Bloc are one of most oil exploration in Indonesia especially in South Kalimantan. Since 1967 Indonesia Government gave the exploration right of Mahakam Bloc to Total Exploration & Production Company. Unit 2017 the exploration right was limitted and Pertamina Company as a state corporate want to be a company that have a exploration right in Mahakam Bloc. The writer collects data from books, encyclopedia, journal, mass media and websites to analyze the strategy of Pertamina Company in take controll of fuel and oil exploration rights from Total Exploration and Production Company in Mahakam Bloc. The theories applied in this research are neoliberalisme perspective with the international cooperation theory. The conclution of this research are the strategy of Pertamina Company in take controll of fuel and oil exploration rights from Total Exploration and Production Company in Mahakam Bloc are done by Pertamina Company have done meeting with Indonesia Government in lobby of Mahakam Bloc exploration, Pertamina Company prepare a facility in take controlling exploration oil from Mahakam Bloc, Pertamina Company cooperation with Total E&P Company as a contractor oil Mahakam Bloc, Pertamina Company used IRRS in support Pertamina to oil exploration. Key words: strategy, oil, exploration, Mahakam.